2021
DOI: 10.3390/catal11020195
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supports BET Surface Areas on Membrane Electrode Assembly Performance at High Current Loads

Abstract: In this work, we investigated the influence of catalyst supports, particularly Brunauer, Emmett, and Teller (BET) surface area of the catalyst support materials, on membrane electrode assembly (MEA) performance. Keeping the anode catalyst layer (CL), membrane, Pt loading, and operating condition unchanged, we prepared cathode CLs using catalysts of identical Pt content (30 wt% Pt) which were supported on carbon black materials having different BET surface areas. We observed optimum cell voltage at high current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Their research showed evidence that, at low current loads, high surface area supports performed best, as expected. The unexpected result was that, at high current loads, medium surface area materials (200 m 2 g −1 ) showed better performance due to mass transport losses and water accumulation in the smaller pores of the high surface area materials [94].…”
Section: Surface Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Their research showed evidence that, at low current loads, high surface area supports performed best, as expected. The unexpected result was that, at high current loads, medium surface area materials (200 m 2 g −1 ) showed better performance due to mass transport losses and water accumulation in the smaller pores of the high surface area materials [94].…”
Section: Surface Areamentioning
confidence: 99%
“…Zhang et al [90] created a chitosan-based carbon catalyst with an extremely high surface area of 1190 m 2 g −1 , which showed excellent activity toward ORR. Interestingly, Mohanta et al [94] investigated the effect of carbon catalyst support surface area at different current loads and discovered that the surface area may require tailoring to the specific conditions of the fuel cell. Their research showed evidence that, at low current loads, high surface area supports performed best, as expected.…”
Section: Surface Areamentioning
confidence: 99%
“…Recently, porous carbons such as Ketjen black, porous carbon nanofiber, and high surface carbon have been widely used and investigate as a support of Pt catalysts because of their high surface area and inside pores. It can be lead to high Pt dispersion on the carbon supports, resulting in improved ORR activity and durability [13][14][15][16][17]. In this study, we investigated the influence of SiO 2 -coated Pt catalysts on cell performance when Ketjen black, known as one of the porous carbons, was used as a support for cathode catalysts.…”
Section: Introductionmentioning
confidence: 99%